(untitled) (Research, Society and Development, 2020)
The present study has the following objectives: to identify the professionals’ knowledge about changes in mental health care from the asylum to the psychosocial model in primary care services; understand how professionals who work in primary care perform their mental health practices to promote the psychosocial model. Method: exploratory, descriptive study, of a qualitative nature, developed with thirty professionals, seventeen nurses, four doctors (five), five psychologists (four) and four social workers, who work in the Family Health Strategies of municipalities in Rio Grande do Sul. The data were collected through semi-structured interviews in April 2018. The analysis technique was Thematic Analysis. Results: through the analysis, two thematic groups were identified: (1) The professionals’ knowledge about changing the asylum to the psychosocial model; (2) Practices that professionals perform in mental health in Primary Care. Final considerations: The low knowledge of professionals about mental health in primary care contributes to the actions being based on referrals, compromising the logic of the paradigm shift from the asylum to the psychosocial model with mental health actions carried out in Primary Care services.